Distribution Patterns and Ecological Determinants of Suitable Habitats for the Dhole (Cuon alpinus) in China - Yuangang Yang; Peng Luo; Yu Zhao; Tongzuo Zhang; Feng Jiang; Zhangqiang You (Animals, 2025)
As a keystone predator within forest ecosystems, the dhole (Cuon alpinus) plays a pivotal role in shaping the population structure and dynamics of these biomes. In China, dhole populations have experienced a dramatic decline, primarily due to habitat loss and fragmentation, poaching, and other historical factors. However, the distribution patterns of suitable habitats and the key environmental factors influencing their suitability remained unclear. In this study, we employed the MaxEnt model to assess the habitat suitability for dholes across China. The results revealed that the primary factors influencing the distribution of potential suitable habitats for dholes were the mean diurnal range (Bio2), temperature seasonality (Bio4), minimum temperature of the coldest month (Bio6), and elevation. Potentially suitable habitats were predominantly located in the central-western and northwestern regions, with scattered distributions in the southeastern parts of China, while areas of high suitability were mainly concentrated in the central-western region. The proportion of suitable habitats varied significantly among the nine provinces analyzed. This study clarified the distribution patterns of suitable habitats and identified the key environmental constraints affecting dhole distribution in China. The findings provide critical ecological data to support the conservation and management of dholes in the region.